The Factors Influencing Material Wastage on Construction Site - Ngu, Chieng Huang; Seow, Ta Wee (Research in Management of Technology and Business, 2024)
This study addresses building waste by identifying significant contributors and proposing viable solutions. Its main research aims are to uncover causes and provide practical solutions to decrease construction waste. The study interviews Gred 7 contractor in Johor Bahru, Malaysia, and prioritises material waste in residential and commercial projects. Despite a small sample size of 86 respondents, informative findings reveal important factors contributing to material waste, including insufficient site management (mean = 4.03), whereas strong inventory control reduces waste and improves construction efficiency. Teaching staff proper methods reduces waste from inefficient activities (mean = 3.92). Inadequate construction monitoring (mean = 3.91), a strong agreement, reduces errors and waste. Waste reduction may be achieved by simplifying operations, using Lean Construction Principles (mean = 3.98), and eliminating non-value-added jobs. Eco-friendly building methods (mean = 3.97), decreasing waste by using recycled resources. Emphasising recyclable resources enhances recycling efficiency and promotes sustainable architecture (mean = 3.94). These findings demonstrate the need for competent management and ecologically friendly waste reduction in construction projects. Further waste reduction requires innovative technology, circular economy concepts, and sustainable material research in building waste management.